Atypical Presentation of Dysembryoplastic Neuroepithelial Tumor - Varis S. Khalilov; Aleksey N. Kislyakov; Natalia A. Medvedeva; Natalia S. Serova (Анналы клинической и экспериментальной неврологии, 2024)
Dysembryoplastic neuroepithelial tumor (DNET) is a benign glioneuronal neoplasm, usually found in children and adolescents, in the vast majority of cases associated with drug-resistant epilepsy. Typically, epileptic seizures are the main, and in most cases, their only clinical manifestation. Although DNET is a benign, biologically stable tumor with few reports of malignancy, it is one of the most common reasons for epileptic surgery. The epileptogenic potential of this tumor is so high that DNET s, along with ganglioglioma, have received the informal term “epileptomas” and are by far the leaders in the group of low-grade tumors associated with long-term epilepsy-associated tumors (LEAT). It is believed that this epileptogenicity is due to localization in the neocortex and frequent association with focal cortical dysplasias (FCD). In the world literature, there are only a few mentions of DNET s not associated with epilepsy. The article presents the experience of complex, interdisciplinary diagnosis of DNET in a child without epilepsy who complained of frequent headaches. During a comprehensive MRI examination, a cortical-subcortical pathological substrate was discovered in the left temporal lobe with radiological signs of DNET. During video-EEG monitoring of night sleep, no epileptiform signs were recorded. There was no history of epileptic seizures or other paroxysms. A control MRI revealed a slight increase in the size of the pathological substrate, which was the reason for surgical treatment. Pathological examination revealed microscopic features of DNET. This case of absence of epilepsy in a child with cortical DNET in the temporal lobe cortex suggests that the spectrum of its clinical manifestations and biological behavior is not fully understood and requires further comprehensive study.